Cross‐cultural adaptation of the Chronic Illness Resources Survey in Japanese patients with diabetes. Issue 1 (10th July 2019) - Sato, Miho; Miyoshi, Hideaki; Nakamura, Akinobu; Sumi, Naomi; Kamoshima, Hikaru; Ono, Yuri
Abstract: Aim: The Chronic Illness Resources Survey (CIRS) is a tool for assessing multiple levels of resources for self‐management in people with chronic illnesses. This study aimed to examine the reliability and validity of the Japanese version of the CIRS (CIRS‐J) among patients with diabetes. Methods: This study included 102 Japanese patients with diabetes. Patients completed the CIRS‐J on two occasions with additional measurements, including the multidimensional scale of perceived social support (MSPSS), the summary of diabetes self‐care activities (SDSCA), and the perceived health competence scale (PHCS). The construct validity, internal consistency reliability, and test–retest reliability were evaluated. Results: Factor analysis resulted in six factors. The Cronbach's α coefficient was 0.82, indicating a high internal consistency. The intraclass correlation coefficient was 0.87, indicating that the CIRS‐J is stable over time. The CIRS‐J showed a positive moderate association with MSPSS, SDSCA, and PHCS, with a correlation coefficient value ranging from .34 to .44. Conclusion: This study showed preliminary support for the reliability and validity of the CIRS‐J. The availability of this instrument will help identify the spectrum of resources available for Japanese people with diabetes in both research and practical settings.